Inspiratory muscle training during rehabilitation in successfully weaned hypercapnic patients with COPD. (February 2017) - Dellweg, Dominic; Reissig, Karina; Hoehn, Ekkehard; Siemon, Karsten; Haidl, Peter
Abstract: Background: This study is aimed to evaluate the effect of inspiratory muscle training (IMT) added to rehabilitation in patients with chronic obstructive pulmonary disease (COPD) who remain hypercapnic and use non-invasive ventilation after successful weaning. Methods: Patients received rehabilitation and were randomized to inspiratory muscle or sham training for 4 weeks. The primary outcome was distance walked within 6 min. Secondary outcomes were inspiratory muscle strength, endurance, lung function, and blood gas levels. Results: Twenty-nine patients participated in this study. Walking distance of the sham group increased from 93 ± 52 m at baseline to 196 ± 85 m at week 4 (p = 0.019, 95% CI: 11–196 m). Patients in the IMT group significantly improved their walking distance from 94 ± 32 to 290 ± 75 m (p < 0.0001 [107–286 m]; p = 0.04 [3–186 m] for between-group comparison). Patients in the IMT group increased their maximal inspiratory pressure from −35 ± 8 to −55 ± 11 cmH2 O (p = 0.001; −6 to −33 cmH2 O), while the increase in the sham group failed to reach significance (−29 ± 10 to −37 ± 13 cmH2 O [−22 to 6 cmH2 O]). Inspiratory power increased from 9.6 ± 5.4 to 20.7 ± 9.7 joules/min (2.6–19.5 joules/min, p = 0.003) in the IMT group, while no significant change occurred in the sham group (7.6 ± 4.2 joules/min at study entry and 11.1 ± 6.9 joules/min [−5.2–12.3 joules/min] at study end). Conclusions: Rehabilitation of successfully weaned patients with COPD and persistent hypercapnia significantly improves functional exercise capacity. Additional IMT significantly enhances functional exercise capacity and increases respiratory muscle strength and power. Graphical abstract: Highlights: In hypercapnic COPD patients who use non-invasive ventilation. Inspiratory muscle training (IMT) is feasible. IMT increases inspiratory muscle strength and endurance. IMT increases functional exercise capacity.